Digital shadow economy an extension of shadow economy in Algeria: Definition, causes and consequences - Aymen Salah BENNIHI; Lahcene BOURICHE (university Of Eloued جامعة الوادي, 2020)
The aim of this paper is to shin light on Digital shadow economy and its reality in Algeria. According to the latest estimation of Medina & Schneider (2018) the size shadow economy in Algeria is very important 30.86 % of the official GDP. However, this estimation did not consider the rise of digital shadow economy which can be an important factor in the evolution of this phenomenon in Algeria. Accordingly, an important part of the reality of the shadow economy in Algeria is not accounted for. This can affect the Algerians authority’s intentions to invest in Digital economy as a way to development and the rise of quality of life. It also has a significant impact on official statistics and furthermore the dissuasions made by policy makers.
Intervention
Keywords: Digital shadow economy; Digital economy; shadow economy; estimation approaches; estimation